Valuation of sewage sludge ash as a component of precast concrete - Baeza Brotons, F.; Garcás Terradillos, P.; Payá Bernabeu, J.; Galao Malo, O. (Revista ALCONPAT, 2015)
This paper proposes binary and ternary combinations of sewage sludge ash (SSA) with fly ash, marble dustand rice hull ash, as partial replacement or addition relative to Portland cement in concretes with a similardosage to that used in the manufacture of precast blocks, with very dry consistency given its manufacturingprocess in plant. Several physical-mechanical tests were carried out on concrete and mortar specimens withcuring ages of 28 and 90 days: density, water absorption and compressive strength. It is proved thatreplacing cement by SSA involves a decrease in density and compressive strength compared to thereference sample, however, the combinations of residues significantly improve the characteristics of thecementitious materials. The addition of SSA provided densities and resistances similar to the controlsample and significantly reduces the water absorption.Keywords: sustainability, industrial products, mineral additions.